Co‐expression of CD133+/CD44+ in human colon cancer and liver metastasis. Issue 2 (25th October 2012) - Bellizzi, Antonia; Sebastian, Sinto; Ceglia, Pasquale; Centonze, Matteo; Divella, Rosa; Manzillo, Elvira Foglia; Azzariti, Amalia; Silvestris, Nicola; Montemurro, Severino; Caliandro, Cosimo; De Luca, Raffaele; Cicero, Giuseppe; et al.
Abstract: Although relatively good therapeutic results are achieved in non‐advanced cancer, the prognosis of the advanced colon cancer still remains poor, dependent on local or distant recurrence of the disease. One of the factors responsible for recurrence is supposed to be cancer stem cells (CSCs) or tumor‐initiating cells, which are a population of cancer cells with ability to perpetuate themselves through self‐renewal and to generate differentiated cells, thought to be responsible for tumor recurrence. This study globally approach the possible role of tissue‐derived stem cells in the initiation of colon cancer and its metastatic process in the liver. Fresh surgical specimens from colon cancer, non‐tumor tissue and liver metastasis were obtained directly from the operating room, examined, and immediately processed. CSCs were selected under serum‐free conditions and characterized by CD44 and CD133 expression levels. CD133 + /CD44 + cell populations were then investigated in paraffin‐embedded tissues and circulating tumor cells isolated from peripheral blood of the same group of colon cancer patients. Our data demonstrate that metastatic properties of cell populations from blood and liver metastasis, differently from primitive tumors, seem to be strictly related to the phenotype CD133 positive and CD44 positive. J. Cell. Physiol. 228: 408–415, 2013. © 2012 Wiley Periodicals, Inc.